Enhancing personal financial literacy among young professionals: an impact study - Vicente Salvador, Montaño (2024)
This impact study intends to determine the significant relationship between the posttest score and personal finance topic controlling for the pretest score. From 2019 to 2023, the Business Cluster initiated a program to enhance the Personal Financial Literacy of Young Professionals through the seminar-workshop using the Quasi pretest-posttest experimental design.  The Analysis of Covariance (ANCOVA) results proves a significant relationship exists between the posttest score and finance topic controlling for the pretest score. Moreover, this study confirmed that the seminar-workshop creates an environment conducive to active learning and engagement, positively impacting personal financial learning outcomes. Using the posthoc test proves that Investment is significantly higher than Budgeting, Decision, and Insurance, suggesting that Young Professionals are more interested in increasing their financial literacy investment than in other financial topics.